Application of the Milan System for Reporting Salivary Gland Cytopathology in pediatric patients: An international, multi‐institutional study. Issue 5 (26th January 2022) - Maleki, Zahra; Saoud, Carla; Viswanathan, Kartik; Kilic, Irem; Tommola, Erkka; Griffin, Daniel T.; Heider, Amer; Petrone, Gianluigi; Jo, Vickie Y.; Centeno, Barbara A.; Saieg, Mauro; Mikou, Panagiota; et al.
Abstract : BACKGROUND: Pediatric salivary gland fine‐needle aspiration (FNA) is uncommon with a higher frequency of inflammatory lesions and a small proportion of malignancies. This international, multi‐institutional cohort evaluated the application of the Milan System for Reporting Salivary Gland Cytopathology (MSRSGC) and the risk of malignancy (ROM) for each diagnostic category. METHODS: Pediatric (0‐ to 21‐year‐old) salivary gland FNA specimens from 22 international institutions of 7 countries, including the United States, England, Italy, Greece, Finland, Brazil, and France, were retrospectively assigned to an MSRSGC diagnostic category as follows: nondiagnostic, nonneoplastic, atypia of undetermined significance (AUS), benign neoplasm, salivary gland neoplasm of uncertain malignant potential (SUMP), suspicious for malignancy (SM), or malignant. Cytology‐histology correlation was performed where available, and the ROM was calculated for each MSRSGC diagnostic category. RESULTS: The cohort of 477 aspirates was reclassified according to the MSRSGC as follows: nondiagnostic, 10.3%; nonneoplastic, 34.6%; AUS, 5.2%; benign neoplasm, 27.5%; SUMP, 7.5%; SM, 2.5%; and malignant, 12.4%. Histopathologic follow‐up was available for 237 cases (49.7%). The ROMs were as follows: nondiagnostic, 5.9%; nonneoplastic, 9.1%; AUS, 35.7%; benign neoplasm, 3.3%; SUMP, 31.8%; SM, 100%; and malignant, 100%. Mucoepidermoid carcinoma was the most common malignancy (18 of 237; 7.6%), and it was followed by acinic cell carcinoma (16 of 237; 6.8%). Pleomorphic adenoma was the most common benign neoplasm (95 of 237; 40.1%). CONCLUSIONS: The MSRSGC can be reliably applied to pediatric salivary gland FNA. The ROM of each MSRSGC category in pediatric salivary gland FNA is relatively similar to the ROM of each category in adult salivary gland FNA, although the reported rates for the different MSRSGC categories are variable across institutions. Abstract : The Milan System for Reporting Salivary Gland Cytopathology can be successfully applied for pediatric salivary gland cytology similarly to previously established adult salivary gland cytology. However, there are some notable differences that require additional studies to confirm its clinical validity and its use as a clinical decision tool in the management of pediatric salivary gland lesions.